Altered explorative strategies and reactive coping style in the FSL rat model of depression - Magara, Salvatore; Holst, Sarah; Lundberg, Stina; Roman, Erika; Lindskog, Maria (Frontiers in Behavioral Neuroscience, 2015)
Modeling depression in animals is based on the observation of behaviors interpreted as analogue to human symptoms. Typical tests used in experimental depression research are designed to evoke an either-or outcome. It is known that explorative and coping strategies are relevant for depression, however these aspects are generally not considered in animal behavioral testing. Here we investigate the Flinders Sensitive Line (FSL), a rat model of depression, compared to the Sprague-Dawley (SD) rat in three independent tests where the animals are allowed to express a more extensive behavioral repertoire. The multivariate concentric square field™ (MCSF) and the novel cage tests evoke exploratory behaviors in a novel environment and the home cage change test evokes social behaviors in the re-establishment of a social hierarchy. In the MCSF test, FSL rats exhibited less exploratory drive and more risk-assessment behavior compared to SD rats. When re-exposed to the arena, FSL, but not SD rats, increased their exploratory behavior compared to the first trial and displayed risk-assessment behavior to the same extent as SD rats. Thus, the behavior of FSL rats was more similar to that of SDs when the rats were familiar with the arena. In the novel cage test FSL rats exhibited a reactive coping style, consistent with the reduced exploration observed in the MCSF. Reactive coping is associated with less aggressive behavior. Accordingly, FSL rats displayed less aggressive behavior in the home cage change test. Taken together, our data show that FSL rats express altered explorative behavior and reactive coping style. Reduced interest is a core symptom of depression, and individuals with a reactive coping style are more vulnerable to the disease. Our results support the use of FSL rats as an animal model of depression and increase our understanding of the FSL rat beyond the behavioral dimensions targeted by the traditional depression-related tests.